2005
DOI: 10.1177/030089160509100305
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parenteral Nutrition in Cancer Patients Undergoing High-Dose Chemotherapy Followed by Autologous Peripheral Blood Progenitor Cell Transplantation

Abstract: High-dose chemotherapy followed by autologous bone marrow or peripheral blood progenitor cell transplantation represents a recognized option in the treatment of solid tumors and hematologic diseases. Patients receiving high-dose chemotherapy are traditionally supported with parenteral nutrition with the aim to prevent malnutrition secondary to gastrointestinal toxicity and metabolic alterations induced by the conditioning regimens. Nevertheless, well-defined guidelines for its use in this clinical setting are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Patients receiving high-dose chemotherapy need to be supported with parenteral nutrition [1] . Nutrition therapy can help cancer patients get the nutrients to maintain body weight and performance status, prevent body tissue from breaking down and rebuild tissues [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients receiving high-dose chemotherapy need to be supported with parenteral nutrition [1] . Nutrition therapy can help cancer patients get the nutrients to maintain body weight and performance status, prevent body tissue from breaking down and rebuild tissues [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Poor psychological status, such as depression or anxiety, not only affects the appetite of patients, but also increases side-effects of treatment [7] and impacts well-being of patients [3] . The effects of nutrition on cancer treatment have been studied by many authors [1][2][3] . However, few studies have reported on the association between nutritional and psychological status in the gastrointestinal cancer patients prior to chemotherapy/radiotherapy and treatment tolerance [4,6] .…”
Section: Introductionmentioning
confidence: 99%
“…45,57,58 Research in the 1980s and 1990s mainly concerned the use of PN, with many proponents advocating routine, prophylactic use. 45,57,58 Research in the 1980s and 1990s mainly concerned the use of PN, with many proponents advocating routine, prophylactic use.…”
Section: Methods Of Providing Nutrition Supportmentioning
confidence: 99%